INCLUSIVE D AND DSTAR PRODUCTION IN E+E- ANNIHILATION AT 29 GEV - Ahlen, S; Akerlof, C; Baranko, G; Baringer, P; Beltrami, I; Bender, D; Blockus, D; Brabson, B; Chapman, J; Cho, Y; Chui, S; Cork, B; et al. (1983)
Inclusive production of (D0, D̄0) and D± mesons have been observed in e+e- annihilation at 29 GeV. The signals correspond to R values of R(D0+D̄0)=3.25±1.2 and R(D++D-)=1.35±0.6. D*± production is also observed via the process D*+→D0π+ and its charge conjugate. The D and D* production rates are compared. © 1983 The American Physical Society.